Fermented traditional wine from palm trees: microbial, nutritional attributes and health impacts - Oluwole, Oluwatoyin; Kosoko, Sulaimon; Familola, Oluwagbenga; Ibironke, Olaide; Cheikyoussef, Ahmad; Raheem, Dele; Saraiva, Ariana; Raposo, António (Frontiers in Food Science and Technology, 2023)
Fermented wine from palm trees is gaining more acceptance by consumers given its natural and health promoting attributes. The traditional wine is fermented from the extracted sap of palm trees by microbes, however, excessive contamination by spoilage microorganisms must be avoided, storage conditions must be ensured to foster its natural fermentation. The importance and quality of this locally produced fermented wine will benefit from a better understanding of the scientific knowledge on its micro and macro nutrients. In this review paper, we explore the science of the traditional fermentation process that leads to the sweet, effervescent, milky but alcoholic beverage known as palm wine or toddy. The microbes that are involved in its fermentation (especially yeasts and lactic acid bacteria) are of interest towards realising the potential economic benefits that will be gained from the standard production of palm wine. It is important to emphasize 'sustainability' in the entire value chain of palm wine as an industry starting from its cultivation, to its processing, side streams, storage and consumption. In addition, the packaging materials for the large-scale production of palm wine will need to be eco-friendly when sustainability is considered.